1991
DOI: 10.1093/nar/19.20.5575
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the polyadenyllationm signal from the T-DNA-encoded octopine sysnthase gene

Abstract: We have characterized the polyadenylation signal from the octopine synthase (ocs) gene. This signal directs mRNA 3' end formation at a number of distinct sites. A combination of deletion and linker-substitution analyses revealed that each of these sites is controlled by multiple upstream sequence elements. Upstream sequences relatively far (greater than 80 nt) from the ocs poly[A] sites were found to be needed for functioning of these sites. Upstream sequences nearer to poly [A] sites were also found to be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 18 publications
0
58
0
Order By: Relevance
“…has been documented with at least one other plant poly(A) signal (MacDonald et al, 1991), suggesting that the situation depicted in Figure 2 is a general one for plant genes.…”
Section: Polyadenylation Sicnals In Plant Nuclear Mrna Precursorsmentioning
confidence: 64%
“…has been documented with at least one other plant poly(A) signal (MacDonald et al, 1991), suggesting that the situation depicted in Figure 2 is a general one for plant genes.…”
Section: Polyadenylation Sicnals In Plant Nuclear Mrna Precursorsmentioning
confidence: 64%
“…For example, a downstream element was found to affect the precision of cleavage, but did not influence the processing efficiency (Sanfacon et al, 1991). More dramatic effect was noted in the analysis of ocs and rbcS 3#-UTR, in which the deletion of the downstream element alters or eliminates the use of the poly(A) site (Hunt and MacDonald, 1989;MacDonald et al, 1991). These notions were not pursued further, and hence remained unresolved, but are revisited in this article.…”
Section: Discussionmentioning
confidence: 95%
“…All of these elements are somewhat degenerate in terms of sequence composition; thus, the FUE consists of an extended U+G-rich region situated more than 50 nucleotides upstream from the poly(A) site, the near-upstream element (NUE) is an A-rich region of 6 to 10 nucleotides situated 10 to 30 nucleotides upstream from the poly(A) site, and the CE is a U-rich region centered around the poly(A) site that itself is typically a YA dinucleotide. While mutational analysis has shown that each element contributes to a high-efficiency signal (Mogen et al, 1990(Mogen et al, , 1992MacDonald et al, 1991;Sanfacon et al, 1991;Rothnie et al, 1994;Li and Hunt, 1995), most aspects of the functioning of these elements have not been defined. The results presented in this article indicate that one polyadenylation factor subunit, CPSF30, plays a role of the functioning of the NUE; this is based on the observations that poly(A) sites that are used only in the wild type, and not the oxt6 mutant, possess the characteristic A-rich NUE signature, while sites used only in the oxt6 mutant lack (C) PACs that fall in intergenic regions.…”
Section: Insight Into the Nature Of Plant Polyadenylation Signalsmentioning
confidence: 99%